Experimental investigation of biogas reforming in gliding Arc plasma reactors - Thanompongchart P. (Hindawi Publishing Corporation, 2014)
Biogas is an important renewable energy source. Its utilization is restricted to vicinity of farm areas, unless pipeline networks or compression facilities are established. Alternatively, biogas may be upgraded into synthetic gas via reforming reaction. In this work, plasma assisted reforming of biogas was investigated. A laboratory gliding arc plasma setup was developed. Effects of CH4/CO2 ratio (1, 2.33, 9), feed flow rate (16.67-83.33 cm3/s), power input (100-600 W), number of reactor, and air addition (0-60% v/v) on process performances in terms of yield, selectivity, conversion, and energy consumption were investigated. High power inputs and long reaction time from low flow rates, or use of two cascade reactors were found to promote dry reforming of biogas. High H2 and CO yields can be obtained at low energy consumption. Presence of air enabled partial oxidation reforming that produced higher CH4 conversion, compared to purely dry CO2 reforming process. © 2014 P. Thanompongchart and N. Tippayawong.